Praca polityczno-wychowawcza i nastroje w wojskach lądowych w pierwszych latach po zakończeniu II wojny światowej - Jarno, Witold (Przegląd Nauk Historycznych, 2011)
In second half of 40th. XX century new communist powers in Poland had the small support of the society, therefore they also tried to convince the Polish people to propagated watchwords and views. On the other hand, the communist authorities also aimed at the pacifying the part of society, which did not want to reconcile to new reality. These aims were realized through the development of the apparatus of the safety and armed forces, which made up the pillars of the new authorities. Therefore, communist reign attached large importance to combining soldiers with new system and ideology, what they tried to realize by the extension in the army of the political apparatus. He had to mould among military man political beliefs consistent with views the new authorities. This activity – from the present-day perspective – should rather characterize as indoctrination. In 1945 the effects of the work of the political apparatus were weakly in the army. On this situation had an influence on the low standard of preparing political officers for their work. The political activity in the army was more and more active gradually, what had the connection with campaigns political to concern on the referendum in 1946 and election campaign to lower house of the Polish Parliament in 1947. Led in military districts political training began gradually to fulfill more and more important part in the mould class character of Polish Army. In 1949 began to create party structures in armed forces, meanwhile the membership to the Polish United Working Party became the necessary condition of the military career. All elements of the political work in the army to be designed for creating new side the Polish Army. The political indoctrination leaded to pacification hostile moods among soldiers, which become in the short time the conscious “new citizens” devoted to the new communist authorities and ready to stand up for new ideology in every moment.